Teaching and learning course “Vietnamese Communist Party’s revolutionary policies” applying the CDIO approach at Ho Chi Minh City university of Technology and Education - current state and solutions - Phung, Thế Anh (Journal of Technical Education Science, 2015)
This article focus on researching the reality of teaching and learning subject “Revolution Lines of Vietnam Communist Party” after six years teaching, and base on that propose some solutions to improve the quality of teaching and learning this subject follow CDIO approach at Ho Chi Minh City of University Technology and Education now.